2006
DOI: 10.1007/s10735-006-9042-9
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb group protein Enhancer of Zeste 2: its links to DNA repair and breast cancer

Abstract: The Polycomb group protein EZH2 is a transcriptional repressor involved in controlling cellular memory and has been linked to tumorigenesis in multiple organs. In this review we summarize the current knowledge on the function of EZH2 in cancer, with special focus on breast cancer, and propose a link between EZH2, the homologous recombination pathway of DNA repair, and breast tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…[23][24][25] Recently, several studies have also shown EZH2 to be highly expressed in aggressive tumors, including human breast cancer, prostate cancer and lymphomas. 9,[13][14][15]26,27 The present study showed PcG proteins Bmi1 and EZH2 which are epigenetic chromatin modifier involved in cancer development, 7 to be involved in this malignant progression of HCC. PcGs are chromatin modifiers which have been reported to affect the expression of a number of genes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[23][24][25] Recently, several studies have also shown EZH2 to be highly expressed in aggressive tumors, including human breast cancer, prostate cancer and lymphomas. 9,[13][14][15]26,27 The present study showed PcG proteins Bmi1 and EZH2 which are epigenetic chromatin modifier involved in cancer development, 7 to be involved in this malignant progression of HCC. PcGs are chromatin modifiers which have been reported to affect the expression of a number of genes.…”
Section: Discussionmentioning
confidence: 55%
“…16 EZH2 was not expressed in either the cholangiocyte or hepatocytes in non-tumorous livers, it is conceivable that the EZH2 expression in addition to the Bmi1 expression may therefore be a predictor of the biological aggressiveness and poor prognosis in HCC and HC-CC as reported in carcinomas in other organs. 9,[13][14][15]26,27,29 Since the extensive expression of Bmi1 and EZH2 was demonstrated in HCC and HC-CC, especially in an aggressive subgroup, Bmi1 and EZH2 may therefore be an effective therapeutic target molecule for advanced HCC and HC-CC. The findings of both the present study and several previous studies showed that the knockdown of Bmi1 and EZH2 using siRNA can induce growth inhibition while reducing metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Ezh2 (polycomb group protein enhancer of zeste homolog 2) is the histone methyltransferase catalytic subunit of the polycomb-repressive complex 2, being overexpressed in a variety of aggressive breast cancers (28,29). Ezh2 is associated with genome instability, disruption of mammary ductal morphogenesis (30), and invasion and metastasis of malignant breast cancer, being partly accounted for by suppression of E-cadherin and induction of MMPs expression (31,32). Ezh2 transcript, protein, and cell content à , significant as compared with control diet (P < 0.05); Ãà , significant as compared with control diet (P < 0.002).…”
Section: Mmtv-pymt Mesenchymal-epithelial Transition In Response To Mmentioning
confidence: 99%
“…Histone H3, one of the five main histone proteins, is a chromatin structural component found in eukaryotic cells (Bhasin et al, 2006). Increasing the levels of H3K27me3 may contribute to the aggressiveness of cancer in various tumors like brain (Smits et al, 2010), breast (Zeidler et al, 2006;Kleer, 2009), kidney (Wagener et al, 2008), lung (Crea et al, 2011), lymphoma (Be´guelin et al, 2013;Yan et al, 2013), and prostate (Takawa et al, 2011). As EZH2 inhibition may lead to transcriptional repression of the affected target gene, the development of potent EZH2 inhibitors has become an attractive therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%